2020
DOI: 10.3390/nu12103186
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect of Boswellic Acid on Bone Metabolism and Possible Mechanisms of Action in Experimental Osteoporosis

Abstract: Estrogen is instrumental in the pathological process of osteoporosis because a deficiency of this hormone increases the release of bone-resorbing cytokines. Acetyl-11-keto-β-boswellic acid (AKBA), a constituent from Boswellia serrata, has an anti-inflammatory effect by inhibiting tumor necrosis factor-α (TNF-α) expression, which leads to a decline in receptor activator of nuclear factor-kappa B (NF-κB) ligand, and consequently, a reduction in osteoclast activity. Hence, AKBA may be beneficial against bone loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…The effects of the above botanical compounds on osteoblasts and osteoclastsmay be mitigated by AM630, which further supports the agonistic effect of these botanical compounds on CB2R. Some investigations have reported the regulatory effects of 11-keto-beta-boswellic acid, mangiferin, and orientin, and our results further revealed that these compounds may modulate bone metabolism by targeting CB2R [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. To the best of our knowledge, this is the first study reporting the effects of dihydromethysticin, desmethoxyyangonin, flavokawain A, echinatin, and11-keto-beta-boswellic acid on osteoblasts and osteoclasts.…”
Section: Discussionsupporting
confidence: 83%
“…The effects of the above botanical compounds on osteoblasts and osteoclastsmay be mitigated by AM630, which further supports the agonistic effect of these botanical compounds on CB2R. Some investigations have reported the regulatory effects of 11-keto-beta-boswellic acid, mangiferin, and orientin, and our results further revealed that these compounds may modulate bone metabolism by targeting CB2R [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. To the best of our knowledge, this is the first study reporting the effects of dihydromethysticin, desmethoxyyangonin, flavokawain A, echinatin, and11-keto-beta-boswellic acid on osteoblasts and osteoclasts.…”
Section: Discussionsupporting
confidence: 83%
“…Orally administered AKBA exerts anti-arthritic activity in bovine serum albumin-induced arthritis. Additionally, AKBA inhibits the toll-like receptor-mediated activation of monocytes through the downregulation of LPS-induced nitric oxide, IL-β, and TNF-α production [ 18 , 19 , 20 , 21 ]. Therefore, this study used βBA to develop a therapeutic agent against bone diseases, which has higher absorption efficiency in vivo than AKBA, may be effective as a drug.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 12 types of BAs of which α-boswellic acid (αBA), β-boswellic acid (βBA), keto β-boswellic acid (KBA), and acetyl-keto β-boswellic acid (AKBA) are the major ones [ 19 ]. Previous studies reported that AKBA inhibits osteoclastogenesis by suppressing the NF-κB-induced TNF-α signaling pathway [ 20 ] and attenuates titanium particle-induced osteogenic inhibition via the GSK-3β/β-catenin signaling pathway [ 21 ]. However, the biological effects of βBA on osteoclast differentiation and bone resorption remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In a rat model of osteoporosis, administration of 35 mg/kg AKBA for 42 days resulted in significant improvement in calcium content and bone mineral density ( p < 0.01 for both) and downregulation of NF-κB and NF-κB-regulated gene expression, suggesting that AKBA has a role in management of postmenopausal osteoporosis through inhibition of osteoclastogenesis. 61 …”
Section: Boswellic Acids Mechanism Of Actionmentioning
confidence: 99%